The post-VTE functional status scale for assessment of functional limitations in patients with venous thromboembolism: Construct validity and responsiveness in a prospective cohort study. Issue 221 (January 2023) - Steiner, Daniel; Nopp, Stephan; Weber, Benedikt; Schlager, Oliver; Königsbrügge, Oliver; Klok, Frederikus A.; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: A large proportion of patients experience functional limitations after an acute episode of venous thromboembolism (VTE). Recently, the post-VTE functional status (PVFS) scale was proposed to capture these limitations. We performed a prospective cohort study to validate this scale. Methods: The PVFS scale, PROMIS physical function 10a, EQ-5D-5L, and disease-specific quality of life (VEINES-QOL/Sym, PEmb-QoL) were assessed within three weeks of VTE diagnosis and after a median (IQR) follow-up of 13.4 (12.7–15.9) weeks. To evaluate construct validity of the PVFS scale, we determined correlations of PVFS scale with the other health measurements and investigated differences in patients above/below 70 years. Responsiveness was evaluated with a linear regression model, predicting change in PROMIS with change in PVFS scale. Results: We included 211 patients (median (IQR) age: 55.1 (44.1–67.6) years, 40 % women). Pulmonary embolism was diagnosed in 105 (49.8 %) patients and 62.6 % of events were unprovoked. The PVFS scale correlated with PROMIS physical function (Spearman's rho (r): −0.67 and −0.63, p  < 0.001) and EQ-5D-5L index ( r  = −0.61 and −0.61, p  < 0.001) at baseline and follow-up. Furthermore, PVFS correlated moderately to strongly with disease-specific quality of life. Patients >70 years had significantly higher PVFS grades at follow-up (median (IQR): 2 (0–3) vs. 1 (0–2), p  = 0.010). Changes in PVFS scale over time were significantly associated with changes in PROMIS physical function. Conclusions: The PVFS scale showed adequate construct validity and responsiveness in a prospective cohort study of patients with VTE, suggesting that it can be incorporated as additional health measurement and outcome parameter in research and clinical practice.